Clinical and In Vitro Resistance of Plasmodium falciparum to Artesunate-Amodiaquine in Cambodia. (27th May 2020) - Mairet-Khedim, Melissa; Leang, Rithea; Marmai, Camille; Khim, Nimol; Kim, Saorin; Ke, Sopheakvatey; Kauy, Chhayleang; Kloeung, Nimol; Eam, Rotha; Chy, Sophy; Izac, Brigitte; Mey Bouth, Denis; et al.
Abstract: Background: Artesunate-amodiaquine is a potential therapy for uncomplicated malaria in Cambodia. Methods: Between September 2016 and January 2017, artesunate-amodiaquine efficacy and safety were evaluated in a prospective, open-label, single-arm observational study at health centers in Mondulkiri, Pursat, and Siem Reap Provinces, Cambodia. Adults and children with microscopically confirmed Plasmodium falciparum malaria received oral artesunate-amodiaquine once daily for 3 days plus single-dose primaquine, with follow-up on days 7, 14, 21, and 28. The primary outcome was day-28 polymerase chain reaction (PCR)-adjusted adequate clinical and parasitological response (ACPR). An amodiaquine parasite survival assay (AQSA) was developed and applied to whole genome sequencing results to evaluate potential amodiaquine resistance molecular markers. Results: In 63 patients, day-28 PCR-adjusted ACPR was 81.0% (95% confidence interval [CI], 68.9–88.7). Day 3 parasite positivity rate was 44.4% (28/63; 95% CI, 31.9–57.5). All 63 isolates had the K13 (C580Y) marker for artemisinin resistance; 79.4% (50/63) had Pfpm2 amplification. The AQSA resistance phenotype (≥45% parasite survival) was expressed in 36.5% (23/63) of isolates and was significantly associated with treatment failure ( P = .0020). Pfmdr1 mutant haplotypes were N86/184F/D1246, and Pfcrt was CVIET or CVIDT at positions 72–76. Additional Pfcrt mutations were not associated with amodiaquine resistance, but the G353V mutant allele was associated with ACPR compared to Pfmdr1 haplotypes harboring F1068L or S784L/R945P mutations ( P = .030 and P = .0004, respectively). Conclusions: For uncomplicated falciparum malaria in Cambodia, artesunate-amodiaquine had inadequate efficacy owing to amodiaquine-resistant P. falciparum . Amodiaquine resistance was not associated with previously identified molecular markers. Abstract : Artesunate-amodiaquine has inadequate efficacy in Cambodian patients with uncomplicated falciparum malaria. Amodiaquine resistance is present in Cambodia and not associated with molecular markers reported in Africa and South America.